POLA PEMBERIAN AIR UNTUK BUDIDAYA MELON - Herawati, Henny
Abstract: Melon is one of the agribusiness crops which nowadays becomes one of the fruit commodities in Indonesia. The cultivation of melon in Indonesia is quite recent that it needs a deeper knowledge on the sort of soil, watering system, crop diseases, fertilizer, etc. Water requirement is calculated as the product of crop coefficient, Kc, and referenced evapotranspiration of each location. A research in tropical region shows that crop coefficient varies with growing stages. At the growing stage (Vegetative), the crop coefficient, K, is 1.151 for the age of 0 to 10 days, 1.829 for the age of 10 to 20 days and 1.902 for 20 to 30 days of age. At the fruit stage (generative), KQ = 2.034 for the age of 30 to 40 days, 1.881 for the age of 40 to 50 days and 1.421 for 50 to 60 days of age. And at the fruit riping stage, an age of 60 to 65 days, the K, is 1.346. Based on the crop coefficient, Kg\'s, above, the net water requirement (including effective rainfall at location), at the growing stage (vegetative), is 0.65 - 1.0 liter/second/hectare, at the fruit stage (generative) is 1.0 - 1.25 liter/second/hectare and at the fruit riping stage, the KK is 0.8 -0.9 liter/second/hectare. Besides, melon can grows in both rainy and dry seasons, so that a rotated planting system can be used provided that the water requirement is fulfilled. It also occurs that the frequency ofplanting at certain location is two times and can be planted again after another planting such as rice.